Remdesivir is efficacious in rhesus monkeys exposed to aerosolized Ebola virus - Travis K. Warren; Christopher D. Kane; Jay Wells; Kelly S. Stuthman; Sean A. Van Tongeren; Nicole L. Garza; Ginger Donnelly; Jesse Steffens; Laura Gomba; Jessica M. Weidner; Sarah Norris; Xiankun Zeng; et al. (Scientific Reports, 2021)
Abstract Efficacious therapeutics for Ebola virus disease are in great demand. Ebola virus infections mediated by mucosal exposure, and aerosolization in particular, present a novel challenge due to nontypical massive early infection of respiratory lymphoid tissues. We performed a randomized and blinded study to compare outcomes from vehicle-treated and remdesivir-treated rhesus monkeys in a lethal model of infection resulting from aerosolized Ebola virus exposure. Remdesivir treatment initiated 4 days after exposure was associated with a significant survival benefit, significant reduction in serum viral titer, and improvements in clinical pathology biomarker levels and lung histology compared to vehicle treatment. These observations indicate that remdesivir may have value in countering aerosol-induced Ebola virus disease.